THE IMPORTANCE OF DEVELOPING INFORMATION AND ANALYTICAL COMPETENCE THROUGH INTEGRATION (Scientific journal of the Fergana State University, 2024)
This article discusses the complexities arising from the rapid and reliable acquisition of information due to the development of telecommunications in modern society. It analyzes the issues related to the reliability of information delivery and the unique competencies required from the information provider. Additionally, it explains the relevance of integrating information and analytical competence among educators and the need to develop these competencies in an interconnected manner. The article also addresses the growing demand for professionals who can conduct in-depth analytical assessments of information, filter data, and distinguish reliable sources.